Entrepreneurship and resource based view: a teaching case study at Mundo Verde - Silva, Nuno Maria Múrias Roquette Cornélio da (2015)
This case study is based in Mundo Verde, a Brazilian natural products company, and its focused on the strategic decisions the company has to make to overcome the current problems. The case is built around three major theoretical perspectives: Competitive advantages from a Resource Based View, Brand Identity and Entrepreneurship. In the case is presented first the company, disclosing the necessary information to analyze and comprehend Mundo Verde, by accurately identifying the company´s competitive advantages. Next the student is presented to a narrative where the CEO of the company meets one of the franchisees in an attempt to find out more about the company´s issues and to see how the stores are working. Several scenarios are presented to the students which represent several possibilities of action, considering the company, the problems to be addressed and the objectives of the company.